Assessment of the development of reflection skills among BED students in Jimma University - Sharew, Mulugeta; Melese, Wudu (Papanda Publishier, 2025)
Currently, there is concern from educational scholars on pre-service teachers training in equipping them with reflective skills. This study intended to assess the development of reflection skills among 3rd and 4th year BED students at Jimma University. A survey research design was employed to answer the objective of the research. 109 male and 94 female BED students across 11 departments were participated in filling out reflection questionnaires and the selection of respondents was carried out using census sampling techniques. Data was analyzed using descriptive statistics to describe the student teachers' extent of reflection in the four scales whereas the t-test for comparison of the difference between gender and batch of students in the Habitual Action scale. Mann Whitney U-test to measure the groups’ sum of rank difference on Understanding, Reflection, and Critical Reflection based on gender and batch. The finding of the study indicated that the level of BED students' habitual action scale was lower and the understanding and reflection were higher. The t-test and u-test analyses disclosed that there was a statistically significant difference in habitual action scale between genders and no statistically significant difference between groups of sex and batch on understanding, reflection, and critical reflection respectively. It was concluded that the reflective skills in BED students were not uniformly and developmentally increasing among the students’ batch and sex. Therefore, it is imperative to work hard to equip BED students with reflective skills particularly critical reflection to help them lifelong learners in their teaching career.